PENINGKATAN EFEKTIVITAS PRODUKSI MELALUI ANALISIS MANUFACTURING CYCLE EFFECTIVENESS (MCE) PADA LINI PERAKITAN EXCAVATOR TIPE PC-135F: Indonesia, Inggris - Hafshin Salman Alfarisy; Ibnu Siswanto (Department of Automotive Engineering Education, Faculty of Engineering, Yogyakarta State University, 2025)
Abstract This research aims to determine the level of effectiveness of the PC-135F Excavator production process in the Medium Size Division of the Assembling Plant of PT. ZX due to delays in completing the product. Manufacturing Cycle Effectiveness (MCE) is a method used to determine the level of effectiveness in the production process. Activity analysis is used to determine cycle time which consists of: processing time, inspection time, transfer time, and waiting/storage time. The research results show that in current conditions the effectiveness value of the PC-135F Excavator production line is 45%. This shows that the production process is still below the ideal figure, namely 100%. After identifying the root of the problem, potential solutions were obtained to minimize delays in the production process of the PC-135F Excavator unit, namely (1) Planning a multi-supplier system for raw material components (2) Planning a safety stock system for raw material components, Manufacturing Cycle Effectiveness (MCE) values increased to 75%. So it can be said that efforts to improve the production line have an impact on increasing the Cycle Effectiveness value. Keywords : Manufacturing Cycle Effectiveness, Productivity, Non-Value Added Activities, Cycle time Abstrak Penelitian ini bertujuan untuk mengetahui tingkat efektivitas proses produksi Excavator PC-135F pada divisi Medium Size Pabrik Perakitan (Assembling Plant) PT. ZX dikarenakan terjadi keterlambatan dalam menyelesaikan produk. Manufacturing Cycle Effectiveness (MCE) adalah metode yang digunakan untuk mengetahui tingkat efektivitas pada proses produksi. analisis aktivitas digunakan untuk menentukan Cycle time yang terdiri dari : waktu pemrosesan, waktu inspeksi, waktu pemindahan, dan waktu tunggu/penyimpanan. Hasil penelitian menunjukkan bahwa kondisi sekarang ini nilai efektivitas pada lini produksi Excavator PC-135F yaitu sebesar 45%. Hal ini menunjukkan bahwa pada proses produksi tersebut masih di bawah angka idealnya yaitu 100%. Setelah dilakukan identifikasi akar masalah diperoleh potensi solusi dalam meminimalisir keterlambatan pada proses produksi unit Excavator PC-135F yaitu (1) Perencanaan sistem multi supplier komponen bahan baku (2)Perencanaan sistem safety stock komponen bahan baku, nilai Manufacturing Cycle Effectiveness (MCE) meningkat menjadi 75%. Sehingga dapat dikatakan bahwasanya upaya perbaikan lini produksi memberikan dampak terhadap peningkatan nilai Cycle Effectiveness. Kata kunci : Efektivitas Siklus Manufaktur, Produktivitas, Aktivitas Bukan Nilai Tambah, Waktu siklus